“Who’s got the infants in mind?” A qualitative exploration of the barriers and enablers to commissioning parent-infant relationship services in England - Lorraine McSweeney; Karen Bateson; Wook Hamilton; Bronia Arnott (BMC Health Services Research)
Abstract Background The earliest relationships between babies and their caregivers can act as a risk factor for social and emotional wellbeing in infancy and impact on later development. Difficulties in parent-infant relationships (PAIR) are characterised by inequalities, with families experiencing adversity at greater risk. In the absence of support, these relationship problems may require later, more expensive services. Interventions exist to address PAIR difficulties but are not widely commissioned, with regional disparities, and infants being under-served. This project qualitatively explored barriers and enablers to commissioning PAIR services. Methods Individuals with commissioning responsibilities relating to PAIR working in Clinical Commissioning Groups or Local Authorities in the North East North Cumbria (NENC) region were invited to participate. Qualitative semi-structured interviews were informed by a topic guide developed through practitioner involvement. Nine interviews were completed online between February and April 2022. Anonymised transcripts were analysed using Framework Analysis. Results Barriers and enablers to commissioning were general, specific to PAIR services, or related to the pandemic context. General factors included the nature of the commissioning process, the importance of taking a collaborative approach to commissioning and the constraints of funding processes. Commissioners valued being able to demonstrate impact and value for money through service evaluation but faced challenges in doing so. Specific barriers relating to PAIR commissioning included a lack of awareness of the importance of infant mental health although there was an acknowledgement of the importance of maternal and parent-infant services/support during the early years. Factors amenable to change were mapped on to the Behaviour Change Wheel to inform the future co-development of a resource to address barriers and enablers. Conclusions This paper is the first to report a pragmatic, applied qualitative exploration of barriers and enablers to commissioning parent-infant relationship services. Insights from commissioners with a wide range of portfolios identified key factors operating at the individual level which were amenable to change. In addition, there were barriers beyond the individual level, such as funding. Using a pragmatic approach, we identified best-fit behaviour change initiatives to develop a commissioning support toolkit to increase access to support, improve outcomes, and decrease inequalities, addressing infants as an under-served group.